Examining the Effectiveness of the Smoking Prevention Program "I Do Not Smoke, I Exercise" in Elementary and Secondary School Settings. Issue 6 (November 2016) - Kolovelonis, Athanasios; Goudas, Marios; Theodorakis, Yannis
The aim of the study was to examine the effectiveness of the smoking prevention program "I do not smoke, I exercise" implemented with elementary and secondary school students. "I do not smoke, I exercise" is a theory-based smoking prevention program that promotes exercise as an alternative of smoking. The program consists of eight sessions implemented weekly. Participants were 338 Greek students (135 elementary and 203 secondary students) who were pre- and posttested in smoking, program, and exercise-related measures. The results showed that the program had significant effects on elementary students' attitudes toward smoking, intention to smoke, subjective norms, attitudes toward the application of the program, and knowledge about the health consequences of smoking. For secondary students, significant effects were found on students' perceived behavioral control and knowledge about the health consequences of smoking, while very few students reported a smoking experience before and after the intervention. Therefore the program "I do not smoke, I exercise" may have positive effects on variables related with smoking behavior. Differences in the program's impact on elementary and secondary students were identified. All these are discussed with reference to the need of implementing smoking prevention programs in schools contexts.